Comparative aspects of volatile fatty acid production in the rumen and distal fermentation chamber in Svalbard reindeer - Sørmo, W.; Haga, Ø.E.; White, R.G.; Mathiesen, S.D. (Rangifer, 1997)
Microbial fermentation end products were investigated in Svalbard reindeer at two different locations, on Nordenskioldland (NL) (n=7) and in a marginal area on Nordaustlandet (NA) (n=11), at different seasons. The pH ranged from 6.51-6.70 in rumen contents and from 6.78-7.17 in the distal fermentation chamber (DFC=caecum and proximal part of the colon) on NL compared to 6.10-6.71 in rumen contents and 6.50-7.35 in DFC contents on NA. The ruminal volatile fatty acid concentration ([VFAJ) was 84.5 ± 9.5 mmol/l compared to 63-9 ± 17.6 mmol/kg in the DFC on NL in winter. In autumn, ruminal and DFC [VFA] was high at 113.5 ± 13.0 mmol/l and 90.4 ± 10.9 mmol/kg, respectively. On NA ruminal [VFA] was 85.7 ± 12.4 mmol/l and 59-6 ± 1.3 mmol/kg in the DFC in winter, compared to 107.3 ± 18.4 mmol/l and 102.0 ± 12.7 mmol/kg in rumen and DFC, respectively, in summer. Mean acetate/propionate (A/P) ratios in the rumen indicate fermentation in favour of plant fibre digestion in winter (4.8) but not in autumn (3.0) on NL. On NA, the mean A/P ratio was 5.1 in winter, compared to 4.6 in summer. In all DFC investigated the A/P ratio was higher than 8.9. The initial ruminal [VFA] did not reflect the VFA production measured. On NL, the production rate of VFA was low or not detectable in rumen and DFC in winter, while in autumn the total production rate of VFA was 59.3 kJ/kgW0 75/d, of which 6.5% originated from the DFC. On NA in winter, a total of 121.3 kJ/kgW0 7S/d was estimated of which 17% originated from the DFC, compared to a total of 380.4 kj/kgW0.75/d in summer where the DFC only contributed 2.7%. Plants (grasses and mosses) with low quality in winter do not seem to contribute significantly to the VFA production in rumen and DFC. VFA production in the DFC seems to be of significant importance in reindeer when pastures have low availability but high quality. The concenttation and the rate of VFA production in the DFC contents were not related to the size of the chamber, but to the diet eaten.